PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA N 1 SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Wahluni, Wahluni; Nurhadi, Nurhadi; Maizeli, Annika (Pendidikan Biologi, 2013)
ABSTRACT  The background of the research is motivated by the low results obtained studying biology students. This is caused by the lack of student motivation in learning biology and considers it boring biology class because the material is rote. Realizing that the author implementing learning by applying strategy synergetic teaching. The purpose of the research to determine the effect of the application of strategies active learning type Synergetic Teaching on learning outcomes of student.The type of research is experimental. The population in this study were students of class XI IPA 1 SMAN 1 Sungai Limau Pariaman Academic Year2012/2013. The research was conducted in May 2013. The design of this study isRandomized Control-Group Posttest Only Desingn.  The analysis of the average values obtained experimental class 78,87   and control class 73,83. Hypothesis testing using t-test values obtained t (2.72)> t table (with a 1.72 significance level0.05) means that the hypothesis is accepted. From the analysis of the data whichhave been obtained can be concluded that the use of learning strategies synergetic teaching biology to improve learning outcomes of students in class XI IPA 1SMAN 1 Sungai Limau Kabupaten Padang Pariaman.